2019
DOI: 10.1111/jpn.13094
|View full text |Cite
|
Sign up to set email alerts
|

Montmorillonite improved the intestinal mucosal barrier functions of laying hens in late production

Abstract: This study was conducted to investigate the effects of dietary supplementation with montmorillonite (MMT) on performance, intestinal endotoxin concentration, gut mucosal oxidation status, intestinal morphology and permeability, and immunological barrier function of laying hens during late production. Four hundred and eighty 75‐week‐old laying hens (Lohmann Brown) were randomly assigned to five treatments with eight replicates per treatment and 12 hens in each replicate. The hens were fed the basal diet supplem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 35 publications
5
14
0
Order By: Relevance
“…Gross villus height and crypt depth measures are generally used to assess intestinal structure integrity. The present study showed that hens fed with the diets containing MOA or MEO complex developed higher villus height-to-crypt depth ratio in the small intestine, which was similar to the results of Chen et al [4,8], Wang et al [11], and Yarmohammadi Barbarestani et al [12]. The mechanism through which MOA and MEO complexes inclusion improved the intestinal morphology has been associating with their ability to suppress the intestinal pathogenic bacteria, which may improve the ability of intestinal epithelial cells to regenerate villus and reduce damage to villi caused by harmful bacteria and toxins [10].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Gross villus height and crypt depth measures are generally used to assess intestinal structure integrity. The present study showed that hens fed with the diets containing MOA or MEO complex developed higher villus height-to-crypt depth ratio in the small intestine, which was similar to the results of Chen et al [4,8], Wang et al [11], and Yarmohammadi Barbarestani et al [12]. The mechanism through which MOA and MEO complexes inclusion improved the intestinal morphology has been associating with their ability to suppress the intestinal pathogenic bacteria, which may improve the ability of intestinal epithelial cells to regenerate villus and reduce damage to villi caused by harmful bacteria and toxins [10].…”
Section: Discussionsupporting
confidence: 92%
“…In this study, the MOA and MEO complexes supplementation down-regulated the mRNA expression levels of MyD88, NF-κB p65, and IL-1β and reduced numerically the TLR4 mRNA expression of the ileum, indicating that MOA and MEO complexes may inhibit the in ammatory responses by modulating the signal pathway of TLR4/MyD88/NF-κB. This nding was similar to the results of Chen et al [8], Yang et al [10], and Liu et al [22]. Many harmful bacteria such as E. coli and Salmonella exhibit structural characteristics of the lipopolysaccharide-constructed cell membrane, so they can be recognized by TLR4, and they then transmit signals to activate in ammatory responses.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…*P < 0.05 and **P < 0.01. and barrier integrity (Farhadi, 2005). That the relative mRNA expression of ileal MUCIN-1, ITGB1, and PKC were upregulated by adding montmorillonite revealed that the addition of montmorillonite improved the intestinal barrier function (Hu et al, 2012;Jiao et al, 2015Jiao et al, , 2018Chen J. F. et al, 2019Chen J. F. et al, , 2020; this was caused by the swelling property of montmorillonite, which will cause the volume of intake feed to become larger, slowing down the time of passing through the intestinal tract and promoting the metabolism of intestinal epidermal cells (Subramaniam and Kim, 2015).…”
Section: Discussionmentioning
confidence: 99%